Effect of Herbal Feed Additives on Performance, Immunity, Serum Parameters and E. coli Counts of Broilers under Heat Stress - Rao, Hanumanth (Indian Journal of Animal Nutrition, 2021)
The present experiment was conducted to investigate the effect of different herbal preparations on the performance of broilers. A total of 250 day-old male broiler chicks were randomly divided into five treatment groups with ten replicates of five birds each. The experimental design consisted of; T1: control diet, T2: Herbal powder I (containing Withania somnifera, Phyllanthus emblica, Glycrrhiza glabra, Tribulus terrestris and Asparagas racemosus), T3: Herbal powder II (containing Withania somnifera, Ocimum sanctum, Mangifera indica and Shilajit), T4: Herbal powder III (Ayuce herbal powder), T5: Vitamin E (70 mg per kg) and Se (0.15 mg per kg). The results indicated that supplementation of herbal preparations (T2, T3 and T4), and vitamin E and Se significantly (P<0.05) increased the body weight gain and feed conversion ratio (FCR) of broilers compared to control group at 42 d of age. However, feed intake was not affected by different herbal supplementation at 42 d of age. The Lipid peroxidation, alkaline phosphatase, blood urea nitrogen, serum cholesterol, blood glucose levels and E. coli counts in small intestine were significantly (P<0.05) lower in herbal supplemented groups compared to control and was at par with vitamin E and Se supplemented group. Various carcass parameters, serum total protein, albumin and antibody titer to Newcastle disease (ND) vaccine was similar among the groups. From the results, it could be concluded that poly-herbal preparations can be used as a feed additive for improving performance of broilers during heat stress conditions.